THE ANALYSIS OF TRANSFERRING MESSAGE IN CONSECUTIVE INTERPRETING ON BILINGUAL SEMINAR HELD BY SMK DWIJENDRA DENPASAR BALI - FERRYANTI, NI PUTU (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2017)
Abstract. Language interpreting is the intellectual activity of facilitating oral and sign language communication, either simultaneously or consecutively, between two or more users of different languages. The process of interpreting involves attending the message, concentrating on the task at hand, remembering the message, comprehend the meaning of the message, analyzing the meaning for the message, and visualizing the message non-verbally in which finally reformulating the message in the target language. The aim of this research is to analyze the process of conveying message from the speaker to the hearer in consecutive interpreting at SMK Dwijendra. This is a qualitative type of research. The collected data was presented in descriptive narrative explanatory. As the results, the interpreter at SMK Dwijendra had understood the system in conducting consecutive interpreting. She applied the note taking technique during the interpreting process. Even though, her facial expression while conducting note taking expressed her confusion in finding the equivalent interpretation. Because of repetition, she could keep on track and did not out of frame in interpreting the speakerâ??s utterances as she was confused to organized the speakerâ??s utterances systematically as opening, main or conclusion statement and frequently loss the information.Â Â Â Â Â Â Â Â Â Â Â Key words: Consecutive Interpreting; Interpreter; Messages